Pendugaan Potensi Lestari Ikan Layang (Decapterus spp) yang Didaratkan di PPN Pengambengan - TRIANTINI, S.A NYOMAN PUTRI; Arthana, I Wayan; Pratiwi, Made Ayu (Current Trends in Aquatic Science; Vol 4 No 1 (2021), 2021)
Scad fish is one of the main catches of fisherman who land their fish at Pengambengan Nusantara Fisheries Port (NFP). The method used in this study is the method of observation and interviews. Fish sampling in the study using a simple random sampling. The scad fish species which were found during the study were Decapterus macrosoma and D. kurroides . This study aimed to know about the distribution of fish length frequency, fish growth pattern, the estimation of sustainable fish potential and the estimation of utilization level of Scad Fish in Pengambengan NFP. The distribution frequency of female Scad Fish dominate the class interval of 197 – 204 mm and male Scad Fish dominate the class interval of 169 – 176 mm. The growth patterns of either male and female Scad Fish are negative allometric, with a W = 0,00001L 2,9497  length-weight relationship for male Scad Fish and W =  0,00002L 2,8089 length-weight relationship for female Scad Fish. The estimation of sustainable potential is carried out by using scheafer approach, MSY of Scad Fish acquire arround 2.646,911 ton/year with Fmsy 1123 trip s/year. Based on data from 2009 – 2018, the utilization status of Scad Fish in Pengambengan NFP had undergone three diffrent states, the low and developing state in 2009 – 2017, and the overfishing status in 2018.